After redemption and abandonment: José Antonio Aponte's Libro de pinturas in the field of visual portraiture. - Lugo-Ortiz, Agnes (Colonial Latin American Review, 2021)
The article focuses on José Antonio Aponte's Libro de pinturas in the field of visual portraiture after redemption and abandonment. It mentions advantage of the crisis of empire that intensified with the Napoleonic invasion of the Iberian Peninsula in 1808, the promulgation of a constitutional monarchy. It also mentions medium for both their self-fashioning and for inducing (visual) recognition of majestic sovereignty.